High glycemic index and glycemic load diets as risk factors for insomnia: analyses from the Women's Health Initiative. Issue 2 (11th December 2019) - Gangwisch, James E; Hale, Lauren; St-Onge, Marie-Pierre; Choi, Lydia; LeBlanc, Erin S; Malaspina, Dolores; Opler, Mark G; Shadyab, Aladdin H; Shikany, James M; Snetselaar, Linda; Zaslavsky, Oleg; Lane, Dorothy
ABSTRACT: Background: Previous studies have shown mixed results on the association between carbohydrate intake and insomnia. However, any influence that refined carbohydrates have on risk of insomnia is likely commensurate with their relative contribution to the overall diet, so studies are needed that measure overall dietary glycemic index (GI), glycemic load, and intakes of specific types of carbohydrates. Objective: We hypothesized that higher GI and glycemic load would be associated with greater odds of insomnia prevalence and incidence. Methods: This was a prospective cohort study with postmenopausal women who participated in the Women's Health Initiative Observational Study, investigating the relations of GI, glycemic load, other carbohydrate measures (added sugars, starch, total carbohydrate), dietary fiber, and specific carbohydrate-containing foods (whole grains, nonwhole/refined grains, nonjuice fruits, vegetables, dairy products) with odds of insomnia at baseline (between 1994 and 1998; n  = 77, 860) and after 3 y of follow-up (between 1997 and 2001; n  = 53, 069). Results: In cross-sectional and longitudinal analyses, higher dietary GI was associated with increasing odds of prevalent (fifth compared with first quintile OR: 1.11; CI: 1.05, 1.16; P -trend = 0.0014) and incident (fifth compared with first quintile OR: 1.16; CI: 1.08, 1.25; P -trend < 0.0001) insomnia in fully adjusted models. Higher intakes of dietary added sugars, starch, and nonwhole/refined grains were each associated with higher odds of incident insomnia. By contrast, higher nonjuice fruit and vegetable intakes were significantly associated with lower odds of incident insomnia. Also, higher intakes of dietary fiber, whole grains, nonjuice fruit, and vegetables were significantly associated with lower odds of prevalent insomnia. Conclusions: The results suggest that high-GI diets could be a risk factor for insomnia in postmenopausal women. Substitution of high-GI foods with minimally processed, whole, fiber-rich carbohydrates should be evaluated as potential treatments of, and primary preventive measures for, insomnia in postmenopausal women.